Prevalence and determinants of exercise‐induced left ventricular dysfunction in patients with coronary artery disease. (21st May 2019) - Honegger, Ursina; Walter, Joan E.; Mueller, Deborah; Puelacher, Christian; Schaerli, Nicolas; Twerenbold, Raphael; Badertscher, Patrick; Boeddinghaus, Jasper; Nestelberger, Thomas; du Fay de Lavallaz, Jeanne; Wussler, Desiree; Pfister, Otmar; et al.
Abstract: Background: The phenomenon of exercise‐induced left ventricular dysfunction (LVD) is incompletely understood. Better understanding of its prevalence and determinants might help to address the current potential oversimplification of the relation between physical activity and cardiac health in patients with coronary artery disease (CAD). Methods: We prospectively assessed the prevalence and determinants of exercise‐induced LVD in patients with stable CAD and normal LV function at rest undergoing bicycle rest/stress myocardial perfusion imaging single‐photon emission computed tomography (MPI‐SPECT). Exercise‐induced LVD was defined as a relevant (5% or more) drop in left ventricular ejection fraction after maximal exercise. High‐sensitivity cardiac troponin I/T (Hs‐cTnI/T) and N‐terminal probrain natriuretic peptide (NT‐proBNP) concentrations were measured before exercise to quantify cardiomyocyte injury and hemodynamic cardiac stress, respectively. Results: Among 317 patients, exercise‐induced LVD was present in 83 (26%) patients. Exercise‐induced LVD was associated with the extent of exercise‐inducible myocardial ischaemia as well as transient ischaemic dilatation. Still, 43% of patients developing exercise‐induced LVD did not have functionally relevant CAD. Neither baseline characteristics, nor the quantification of the extent of cardiomyocyte injury and hemodynamic cardiac stress using hs‐cTnI/T and NT‐proBNP concentrations, respectively, allowed predicting exercise‐induced LVD. Conclusion: One out of four patients with stable CAD develops exercise‐induced LVD after bicycle exercise test. While the extent of exercise‐inducible myocardial ischaemia is a predictor, other still unrecognized mechanisms also seem to play a major role, as nearly half of all patients with exercise‐induced LVD do not have functionally relevant CAD.